ZOONOZLAR HAKKINDA BİLGİ DÜZEYİNİ ÖLÇEN BİR ÖLÇEK GELİŞTİRME ÇALIŞMASI - KURT, OSMAN (Fırat Üniveristesi, 2021)
Bu çalışmanın amacı önemli bir halk sağlığı problemi olan zoonozlar hakkında Halk sağlığı uzmanlarının bilgi düzeyini değerlendirmek için bir ölçek geliştirmek ve bu ölçeğin geçerlilik ve güvenirliğini belirlemektir. Ölçeğin geliştirilmesinde ilk aşama olarak kapsam geçerliliği sağlanmıştır. Her madde için madde güçlük indeksi ve madde ayırıcılık gücü indeksi hesaplanmıştır. Yapı geçerliliğini belirlemek için açımlayıcı faktör analizi kullanılmıştır. Ölçeğin güvenilirliğini belirlemek için, Cronbach alfa iç tutarlılık katsayısı hesaplanmıştır. Çalışmamız 01.09.2020-25.11.2020 tarihleri arasında sahada çalışan halk sağlığı uzmanlarına mail yoluyla gerçekleştirilen metodolojik bir araştırmadır. Çalışmanın yapılabilmesi için etik onay ve idari izinler yazılı olarak alınmıştır. Çalışma grubunun 229'u (%56,8) kadın olup yaş ortalaması 37,8±7,5 (min=25-maks=67) olarak bulunmuştur. Çalışmaya katılan halk sağlığı uzmanlarının ortalama uzmanlık süresi 4,8±6,1 yıl olarak bulunmuş olup en fazla oranda il sağlık müdürlüğünde (%48,9) görev yapmaktadırlar. Yine katılımcıların 188'i (%46,7) bulaşıcı hastalıklar şubesinde görev yapmış ya da yapmaktadır. Katılımcıların 214'ü (%53,1) zoonozlar ile ilgili yeterli bilgiye sahip olduğunu düşünürken 378'i (%93,8) zoonozların önemli bir halk sağlığı problemi olduğunu düşünmüştür. Zoonoz Bilgi Düzeyi Ölçeği (ZBDÖ)'nin ortalama zorluk düzeyi 0,68 şeklinde bulunmuş olup maddelerin zorluk dereceleri %32-%98 arasında değişmektedir. ZBDÖ'nün madde ayırt edicilik katsayısı 0,21-0,83 arasında değiştiği görülmüştür. AFA'da KMO 0,829 olarak bulunmuş olup Barlett testi sonucunda p<0,001 olarak belirlenmiştir. Ölçeğin Cronbach alfa değeri 0,910 bulunmuştur. Madde çıkarılmış Cronbach alfa değerleri ise 0,903-0,908 arasında değişmektedir. Bulaşıcı hastalıklar şubesinde çalışmış olanların bilgi düzeyi çalışmayanlardan anlamlı bulunmuştur. Bunun yanında uzmanlık yapma süresi ve bulaşıcı hastalıklar şubesinde çalışma süresi arttıkça bilgi puanının arttığı görülmüştür. Sonuç olarak zoonozlar hakkında geliştirilen bu ölçek geçerli ve güvenilir bulunmuştur. Ölçeğin güvenirliğinin özel gruplarda test edilmesi toplumun diğer alanına uygulanabilmesi açısından önemlidir. Anahtar Kelimeler: Zoonoz, bilgi düzeyi, ölçek geliştirme

The aim of this study is, first, to develop a scale in order to assess the level of knowledge about zoonoses, an important public health problem, and secondly, to determine the validity and reliability of this scale. As the first step of scale development, content validity was ensured. Item difficulty and item discrimination indices were calculated for each item. Exploratory factor analysis (EFA) was used to determine the construct validity and Cronbach alpha internal consistency coefficient was calculated to determine the reliability of the scale. Our study is a methodological research conducted by e-mail to public health experts working in the field between 01.09.2020-25.11.2020. Ethical approval and administrative permissions were obtained in writing in order to conduct the study. Mean age of the public health specialists included in the study was found to be 37.8 ± 7.5 (min = 25-max = 67). 229 (56.8%) of these public health specialists were female. The mean length of service of the public health specialists was found to be 4.8 ± 6.1 years. Provincial health directorates (48.9%) had the highest rate as the workplace of the public health specialists participated in the study. On the other hand, 188 (46.7%) of the participants were found to either have worked before or are still working in the infectious diseases department. 214 (53.1%) of the participants were found to think that they have sufficient knowledge about zoonoses, whereas 378 (93.8%) of them were found to think that zoonoses constitute an important public health problem. Difficulty indices of the items included in the Zoonosis Knowledge Level Scale (ZKLS) ranged from 32% to 98%, and the mean difficulty index for the overall scale was calculated as 0.68. The item discrimination indices of the items included in the ZKLS ranged from 0.21 to 0.83. EFA revealed a Kaiser-Meyer-Olkin (KMO) coefficient of 0.829, and it was determined as a result of the Barlett test that p <0.001. Cronbach's alpha value of the scale was found to be 0.910. The resultant Cronbach alpha values upon deletion of any item from the scale were found to be between 0.903 and 0.908. Scores that the public health specialists that worked in the infectious diseases department obtained from the scale were found to be significantly higher compared to those who did not work in the infectious diseases department. Furthermore, length of service as a specialist as well as the length of service in the infectious diseases department were also found to be positively correlated with the scale score, indicating a higher level of knowledge about zoonoses. In conclusion, a ZKLS has been developed to assess the level of knowledge about zoonoses, and has been found to be valid and reliable based on the respective validity and reliability studies carried out. Testing the reliability of the scale in specific groups however is important in order for the scale to be applied to other segments of the society in addition to the community of public health specialists. Key Words: Zoonosis, knowledge level, scale development
Development of a scale to measure the level of knowledge about zoonoses
Keywords: Halk Sağlığı